1987
DOI: 10.1002/bbpc.19870910708
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dissolved Electrolytes on the Miscibility of Binary Liquid Systems with Closed Miscibility Gaps

Abstract: Electrolytes J Liquids J Solutions J ThermodynamicsThe dependence of the upper and lower critical solution temperatures T, of the systems (1) oxolane + water, and (2) 2-butoxyethanol + water on the mole fraction xEl of dissolved 1-1,2-1, and 3-1 electrolytes has been investigated. The material stability of the homogeneous state of both systems is extremely sensitive to small electrolyte concentrations so that the observed shift of T, may be interpreted as the result of a perturbation of the mutual solvation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The experimen-C 4 E 1 /water, SiO 2 mixtures to lower values compared with tal basis for this finding is broadened by the results reported the system C 4 E 1 /water [T P (C 4 E 1 /water) 0 T P (C 4 E 1 /water, in this contribution: The stability of the dilute dispersion of SiO 2 ) É 1 K]. This is in agreement with the literature (14 homogeneous suspension. The C 4 E 1 minority phase b is free of colloidal particles.…”
Section: Introductionsupporting
confidence: 90%
“…The experimen-C 4 E 1 /water, SiO 2 mixtures to lower values compared with tal basis for this finding is broadened by the results reported the system C 4 E 1 /water [T P (C 4 E 1 /water) 0 T P (C 4 E 1 /water, in this contribution: The stability of the dilute dispersion of SiO 2 ) É 1 K]. This is in agreement with the literature (14 homogeneous suspension. The C 4 E 1 minority phase b is free of colloidal particles.…”
Section: Introductionsupporting
confidence: 90%
“…The binary mixtures of water–LT and water–BE have an LCST at 34 °C (ref. 21) and 48 °C, 24,25 respectively. For the redox species, ferro-/ferricyanide ions (Fe(CN) 6 4−/3− ) were used.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the effect of inorganic salts on the cloud point depends on the ionic species. 24,25,30,31 In previous studies of diverse research elds, many solvent systems have been reported to show the LCST or UCST behaviors, which include not only molecule solvents 21,24,25,31 but also ionic liquids 22,23,30,[32][33][34][35][36][37][38][39] and polymers. 23,[40][41][42] The large number of candidates for the electrolyte components enable the exible tuning of the operation temperature, which will contribute to the utilization of low-grade heat sources in a wide temperature range.…”
Section: Electrolyte Design Focusing On Electrochemical Reactionmentioning
confidence: 99%